How has COVID-19 affected dentistry practice? The perspective of future changes in a comprehensive literature review - Sanaz Soheilifar; Sara Soheilifar; Farahnaz Fahimipour; Jafar Soheilifar; Sepideh Soheilifar; Mohsen Bidgoli; Fatemeh Baharak Ghaedi (Wolters Kluwer Medknow Publications, 2022)
Background: During the early stages of the COVID-19 pandemic, new guidelines were provided for dental offices to prevent the disease transmission. Dentists suffered a lot of financial and psychological damage as a result of the pandemic. Aim: In this article, the authors reviewed the guidelines provided by the Centers for Disease Control (CDC) and the prevalence of the disease among dentists and their patients, COVID-19 vaccination, emerging new variants of the virus, and future perspective. Methods: PubMed, Scopus, Embase, Web of Science, and Cochrane databases were used to find the publications published from December 2019 to the end of December 2021, discussing the challenges that dentists encountered in the COVID-19 pandemic. Interventional, observational, and review articles in any language were included. The contents were analyzed, and results of the original papers were obtained. Results: A total of 94 articles were found through electronic and hand searching. From them, 59 studies were excluded and 35 fulfilled the inclusion criteria. Publications on the prevalence of COVID-19 cross-infection in dental settings reported a low incidence of the disease while adhering to the CDC guidelines. Conclusion: This shows that the special precautions released for the preventive transmission of COVID-19 in dental clinics are effective measures and while high transmissible variants are circulating in the populations, the guidelines should be followed by dental health-care workers, even in communities with high vaccination rates.